Treatment with 1-MCP: an alternative to extend storage in plums harvested with advanced maturity - Candan, Ana Paula; Calvo, Gabriela (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2021)
Maturity at harvest is a determining factor in fruit storage potential, especially in such perishable species as plums (Prunus salicina L.). However, harvest´s logistics is very complex, and a large percentage of fruits are harvested at a more advanced stage of maturity than the optimum recommended for long storage. Treatment with 1-MCP has shown to be effective in reducing the post-harvest deterioration rate of Japanese plums, but the effectiveness of this treatment may be reduced in late harvested fruit. The aim of this trial was to determine the efficiency of treatment with 0.4 μL L-1 of 1-MCP in Larry Ann plums harvested at 4 different maturity stages. The results showed that the treatment was effective in reducing the ripening rate of the fruit at all harvest timings. The duration of this effect and the number of parameters affected decreased as harvest was delayed. In maturity stage 1 (M1, ~62 N) and maturity stage 2 (M2, ~58 N), 1-MCP delayed ethylene production rate during shelf life after 30, 40, and 50 days of storage at 0 ºC and reduced loss of flesh firmness, and acidity. At the maturity stage 3 (M3, ~50N) 1-MCP delayed ethylene production rate during shelf life after 30 and 40 days of storage at 0 ºC and maintained higher flesh firmness values. In fruit harvested at the maturity 4 (M4, ~35 N), 1-MCP did not affec ethylene production rate, but reduced loss of flesh firmness during shelf life, supporting the hypothesis that the treatment has a direct inhibitory effect on softening enzymes, independent of ethylene.